Newer Systemic Fungicides For Neck Blast Disease Management In Rice (Journal of Plant Disease Sciences, 2020)
Five newer and commercially available fungicides were evaluated during five Rabi seasons of Rabi 2012-13, Rabi 2013-14, Rabi 2014-15, Rabi 2015-16 and Rabi 2016-17 against neck blast disease (Pyricularia oryzae) of rice at Rice Research Station, Moncompu, Alleppey District, Kerala. The treatments were kresoxym methy l44.3 SC, tebuconazole 50% + trifloxystrobin 25% 75 WG, tebuconazole 250 SC, carbendazim 50WP with the standard check fungicide iprofenphos48 EC. The confirmative farm trials were conducted at six locations of Kuttanad region during Rabi 2017-18. The new generation fungicide molecule kresoxym methyl 44.3SC@ 1ml/liter water was found most promising fungicide in restrict the neck blast disease (7.84 %) and gave the maximum grain yield (7373 kg/ha) and followed by tebuconazole 250 SC @ 1.5 ml/liter water(8.87 % and 7168 kg/ha), respectively.
Keywords: Rice; Neck blast; Systemic fungicide; Incidence and Yield